ARCADE: A RAN Diagnosis Methodology in a Hybrid AI Environment for 6G Networks - Oliveira, Daniel Ricardo Cunha; Moreira, Rodrigo; Silva, Flávio de Oliveira (Anais do Workshop de Redes 6G (W6G), 2025)
Artificial Intelligence (AI) plays a key role in developing 6G networks. While current specifications already include Network Data Analytics Function (NWDAF) as a network element responsible for providing information about the core, a more comprehensive approach will be needed to enable automation of network segments that are not yet fully explored in the context of 5G. In this paper, we present Automated Radio Coverage Anomalies Detection and Evaluation (ARCADE), a methodology for identifying and diagnosing anomalies in the cellular access network. Furthermore, we demonstrate how a hybrid architecture of network analytics functions in the evolution toward 6G can enhance the application of AI in a broader network context, using ARCADE as a practical example of this approach.